2010
DOI: 10.3366/afr.2010.0403
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Cross-border Trade and Practical Norms in West Nile, North-Western Uganda

Abstract: This article describes how cross-border trade in West Nile, north-western Uganda to a large extent takes place outside of the legal framework. This does not mean that this trade is unregulated. We make use of the concept of ‘practical norms’ to show the existence of regulation within this trade, which diverges both from official norms and social norms (‘moral economy’). The article describes how these practical norms emerged and how they are enforced. First, it is shown how the moral economy of cross-border tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 27 publications
0
60
0
Order By: Relevance
“…Notwithstanding the problems and controversies that have dogged the concept of the 'informal sector' since its inception (Bromley, 1978;Peattie, 1987;Titeca and De Herdt, 2010), it is hard to dispute that certain activities largely circumvent formal state regulation and that 'informality matters' for development (Chen, 2006;Meagher, 2010a). Moreover, Uganda in many ways represents one of the leading examples of economic informalization due to the massive growth of the 'Magendo' black market under Idi Amin and Milton Obote (Kasfir, 1983;Prunier, 1983).…”
Section: From Planning To Governance: Shifting Development Practices mentioning
confidence: 99%
“…Notwithstanding the problems and controversies that have dogged the concept of the 'informal sector' since its inception (Bromley, 1978;Peattie, 1987;Titeca and De Herdt, 2010), it is hard to dispute that certain activities largely circumvent formal state regulation and that 'informality matters' for development (Chen, 2006;Meagher, 2010a). Moreover, Uganda in many ways represents one of the leading examples of economic informalization due to the massive growth of the 'Magendo' black market under Idi Amin and Milton Obote (Kasfir, 1983;Prunier, 1983).…”
Section: From Planning To Governance: Shifting Development Practices mentioning
confidence: 99%
“…It can be seen that cross-border trade stabilizes the market price of the goods supplied with the additional demand from the recipient country and provide job opportunities. However, in terms of tax collection, it is affected by the probability of not paying taxes, as mentioned by Ackello-Ogutu and Echessah (1998), Alusala (2010), Lesser andMoise-Leeman (2009), Macamo (1999), Peberdy (2000), Sikder, (2005 and Titeca & de Herdt (2010). The implication of cross-border trade also have spin-off activities, including human trafficking, smuggling of migrants, the spread of infectious diseases and crime as experienced in Laos, Combodia, Vietnam and Thailand (Paitoonpong, 2007) and at Uganda-Rwanda border (Alusala, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…After the killing of six elephants in Queen in 2015, the conservation area manager stated 'those who come with guns into the park have come to wage war on us' but added that 'rules of engagement will apply and those found with firewood and grazing animals will be prosecuted' (The Citizen, 2016). This suggests that the perceived motivation of offenders influence ranger discretion, and previous research has found that in Uganda, both protected areas and borders (Runhovde, 2017;Titeca & Herdt, 2010) are operated through compromises and discretionary decision-making seeking to sustain a sound relationship with sometimes uncooperative community members. Over time, this could change should law enforcement officers come to regard themselves as being at war with poachers and traffickers.…”
Section: Discretion In Interaction With Offendersmentioning
confidence: 94%